Shumenko O. Part-of –speech parameters of the morden English denumerals - Shumenko O. (Philological Treatises, 2020)
Structural and semantic nature of the modern English denumerals is being analyzed. Part-of- speech parameters of the denumerals are being analyzed. The processes of evolution and involution are being considered.